Oxford Atlas project for pakistan - Khan, Dr Fazle Karim (Karachi : Oxford university press, 2022)
The Atlas Project for Pakistan is a comprehensive resource that presents a detailed overview of Pakistan$1 (Bs geography, history, culture, and development. The book is part of a series designed to offer in-depth analysis and visual representation of the country's key features, with a particular focus on its physical landscapes, political boundaries, socio-economic conditions, and environmental challenges.s
Keywords: Geography : Textbook